Work Discipline, Work Motivation, Employee Performance and Service Quality: A Study on Local Government - Zai, Desliman Jaya; Tinambunan, Aryanto (Jurnal Ilmiah Sumber Daya Manusia, 2025)
Public service quality in Indonesian local governments continues to face challenges in meeting increasingly high public expectations. The phenomenon of low civil servant performance, characterized by work indiscipline and declining motivation, has become a crucial issue directly impacting service quality. This study examines the influence of work discipline and work motivation on employee performance and service quality in local government by integrating Herzberg's Two Factor Theory. Employing a cross sectional quantitative design, data were collected through a survey of 345 civil servants selected using stratified random sampling and analyzed using multiple regression. The findings reveal that motivator factors, particularly achievement (β=0.412, p<0.001) and recognition (β=0.368, p<0.001), are the strongest predictors of both employee performance and service quality. Work discipline also demonstrates a significant effect (β=0.325, p<0.001), while hygiene factors exert only a minimal influence (β=0.089, p>0.05). These results highlight that enhancing intrinsic motivation and enforcing discipline are essential strategies for strengthening employee effectiveness and public service quality. The practical implication is that local governments should prioritize job enrichment policies, performance based rewards, and consistent enforcement of regulations to foster accountability while promoting sustainable civil servant performance.